2020
DOI: 10.1155/2020/8349480
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photocatalytic Activity of TiO2/SnO2 Binary Nanocomposites

Abstract: The paper presents the results of characterization and study of adsorption-photocatalytic properties of commercial and synthesized-by-hydrothermal method TiO2 and TiO2-SnO2 nanocomposites. Hydrothermal synthesis of TiO2-based nanocomposites was performed in two ways: single-stage and two-stage methods. Characterization was carried out by XRD, X-ray fluorescence method, XPS, EPR, PL, and low-temperature adsorption-desorption of nitrogen, which showed that TiO2-SnO2 nanostructured composites were obtained with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Among these, TiO 2 is the most widely utilized photocatalyst due to its unique properties. They in-clude high physical and chemical stabilities, high photocatalytic activity, nontoxicity, large abundance and low cost [60,61]. Besides, TiO 2 employment is preferred in the form of nanostructures, which have improved surface chemistry and increased surface area [62].…”
Section: Heterogeneous Photocatalysis Over Tiomentioning
confidence: 99%
“…Among these, TiO 2 is the most widely utilized photocatalyst due to its unique properties. They in-clude high physical and chemical stabilities, high photocatalytic activity, nontoxicity, large abundance and low cost [60,61]. Besides, TiO 2 employment is preferred in the form of nanostructures, which have improved surface chemistry and increased surface area [62].…”
Section: Heterogeneous Photocatalysis Over Tiomentioning
confidence: 99%
“…The photodegradation mechanism followed pseudo-secondorder kinetics with an efficiency of 78%. Kutuzova et al 205 followed the hydrothermal synthesis method to synthesize a TiO 2 /SnO 2 nanocomposite for photocatalytic cationic and anionic dye degradation. The studies indicated that the nanocomposite showed sorption-photocatalytic properties where the photocatalyst showed higher sorption ability with anionic dyes, whereas it showed higher photocatalytic activity with cationic dyes.…”
Section: Applications Of Snomentioning
confidence: 99%
“…The increased effectiveness of its practical applications may be due to the improved properties, such as increased surface area, chemical and thermal stability, increased surface activities or number of active surface sites, enhanced charge transfer processes, mechanical strength, reduced electron-hole recombination, etc. [21][22][23][24][25][26][27][28][29][30].…”
Section: Sno2 Nanoparticles (Sno2 Nps) and Sno2-based Nanocompositesmentioning
confidence: 99%